subtract:%20(3b%E2%88%922c)%E2%88%92(6c+2b)%E2%88%92(b+c).(1%20point)%0A

1 answer

To simplify the expression \((3b - 2c) - (6c + 2b) - (b + c)\), we can follow these steps:

  1. Distribute the negative signs: \[ = 3b - 2c - 6c - 2b - b - c \]

  2. Combine like terms (group \(b\) terms and \(c\) terms):

    • For \(b\): \[ 3b - 2b - b = 0b = 0 \]
    • For \(c\): \[ -2c - 6c - c = -9c \]
  3. Putting it all together: \[ 0 - 9c = -9c \]

Therefore, the simplified expression is: \[ \boxed{-9c} \]